Assessment of the effectiveness of a data visualization workshop in the development of graphic representation skills: Pre and post implementation comparative study - Soto Umaña, Dylan; Aguilar Fernández, Eduardo; Zamora Araya, José Andrey (IE Revista de Investigación Educativa de la REDIECH, 2025)
The objective of this investigation was to compare the skills related to graphic representations of information in teachers on training at the National University of Costa Rica, before and after the implementation of a data visualization workshop. A workshop on data visualization was implemented and two questionnaires were developed to collect perception information about the students’ skills in data visualization. Student perception was compared using the t-student test for paired measurements and the Wilcoxon-Pratt rank test. The analysis showed that student ratings of their graphic composition skills (p < 0.0001), graphic interpretation (p < 0.0001), optimal representation (p < 0.0001), relationship with other representations (p = 0.0004) and contextual relationship (p = 0.0003) presented significant increases after the implementation of the workshop. Significant progress was achieved in all areas evaluated after the implementation of the workshop, which indicates that the participating students acquired fundamental tools to understand, interpret and properly use statistical graphic representations in different contexts that involve a large amount of information.